2007
DOI: 10.1007/s00027-006-0843-4
|View full text |Cite
|
Sign up to set email alerts
|

Geographic distribution of Tetracapsuloides bryosalmonae infected fish in Swiss rivers: an update

Abstract: Abstract. Proliferative kidney disease (PKD) has been recognized as a potential threat to brown trout (Salmo trutta) populations in Switzerland. A study performed in 2000/2001 on 139 sampling sites from 127 rivers in Switzerland revealed a wide distribution of fi sh infected by Tetracapsuloides bryosalmonae, the causative agent of PKD. The present study aimed to complement this dataset by studying a further 115 sample sites from 91 rivers and 4 fi sh farms. Mainly brown trout were investigated for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
69
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 28 publications
2
69
1
Order By: Relevance
“…This vertical transmission capacity should enable T. bryosalmonae to persist indefinitely in the local bryozoan population without the vertebrate host, representing a potentially very effective dispersal strategy for the parasite. On the other hand, highly heterogeneous distributions of T. bryosalmonae at the micro-geographic scale shown here and by others (Wahli et al 2007, Peeler et al 2008 indicate that the realized dispersal ability of the parasite may be much more restricted. In order to evaluate which of the scenarios holds true for T. bryosalmonae, quantification of the relative roles of drift and gene flow among T. bryosalmonae populations using microsatellite or single nucleotide polymorphism markers would be required.…”
contrasting
confidence: 42%
“…This vertical transmission capacity should enable T. bryosalmonae to persist indefinitely in the local bryozoan population without the vertebrate host, representing a potentially very effective dispersal strategy for the parasite. On the other hand, highly heterogeneous distributions of T. bryosalmonae at the micro-geographic scale shown here and by others (Wahli et al 2007, Peeler et al 2008 indicate that the realized dispersal ability of the parasite may be much more restricted. In order to evaluate which of the scenarios holds true for T. bryosalmonae, quantification of the relative roles of drift and gene flow among T. bryosalmonae populations using microsatellite or single nucleotide polymorphism markers would be required.…”
contrasting
confidence: 42%
“…Several investigations have noted the presence of T. bryosalmonae infections and discussed the possible connection with decreases in populations of infected fish. In Switzerland, it has been suggested that recent decreases in brown trout populations were caused by PKD (Wahli et al 2002(Wahli et al , 2007. A similar scenario is thought to be the case for Atlantic salmon in Norway (Sterud et al 2007), and (Kristmundsson et al 2010) hypothesize that PKD may play a significant role in the recent decline in Arctic charr populations in Iceland.…”
Section: Effects Of Pkd In Wild Fishesmentioning
confidence: 88%
“…It is clear now from several studies that Tetracapsuloides bryosalmonae is widespread in wild hosts in both Europe and North America and that many wild salmonids suffer from PKD (Wahli et al 2007, Okamura et al 2011. While PKD constitutes a serious problem for freshwater production of salmonids in Europe and North America (Hedrick et al 1993, Okamura et al 2011, the effects of T. bryosalmonae infections on wild fish populations are still debatable.…”
Section: Effects Of Pkd In Wild Fishesmentioning
confidence: 99%
See 2 more Smart Citations